Successful intelligence and its relationship to lateral thinking among fifth-graders in mathematics - Haider Mathkhour Mouzan; Natiq Shaheed Farhan; Ahmad Sahl Majid naser (Peerian Journals Publishing, 2024)
The research aims to measure successful intelligence in its three areas of intelligence (analytical, practical and creative) and recognize lateral thinking with its skills (generating new realizations, generating new methods and methods, generating new ideas, generating new alternatives, generating new creations) and knowing the direction and strength of the correlation between successful intelligence and lateral thinking in fifth-graders in mathematics.
Keywords: lateral; knowing; generating